Influencia del talento humano en la gestión financiera de las microempresas comerciales de Machala. - Salinas Poveda, Veronica Jacqueline; Romero Valverde, Leidy Fernanda (Machala : Universidad Técnica de Machala, 2022)
In this integrative project, the influence of human talent on financial management within commercial microenterprises in the city of Machala was analyzed, in this way it is intended to determine how human capital contributes to the profitability and positioning of the organization in a market. A descriptive-sectional methodology was applied in the research since its components are characterized in a certain time, through a bibliographical verification and an analytical control of the collected data, an exploratory, explanatory level was used; a non-experimental design and a deductive method with a quantitative approach. Among the different discoveries suitable for the execution of the investigation, it was detected that human talent influences financial management when possessing skills, being trained and qualified in the area to which it belongs, having skill in the financial domain and resilience, thus preventing the activities empirically; on the other hand, employees must comply with business rules and have interpersonal relationships to achieve efficient work. We worked with a finite sample and an elementary instrument was obtained, such as the survey for the proper collection of information. As a result, 4 essential dimensions were obtained in the study, such as: abilities and skills, professional profile, achievement of objectives and internal policies, which, when carried out effectively, will give way to microenterprises to develop a competitive advantage. Finally, it was concluded that the staff of microenterprises does not have optimal knowledge in financial management.
En el presente proyecto integrador se analizó la influencia del talento humano en la gestión financiera dentro de las microempresas comerciales de la ciudad de Machala, de esta forma se pretende determinar cómo contribuye el capital humano en la rentabilidad y posicionamiento de la organización en un mercado. Se aplicó en la investigación una metodología de índole descriptivo-seccional ya que se caracteriza en un tiempo determinado sus componentes, mediante una verificación bibliográfica y un control analítico de los datos recopilados, se empleó un nivel exploratorio, explicativo; un diseño no experimental y un método deductivo con enfoque cuantitativo. Entre los distintos descubrimientos idóneos para la ejecución de la investigación se detectó que el talento humano influye en la gestión financiera al momento de poseer competencias, estar capacitado y calificado en el área que pertenece, teniendo habilidad en el dominio financiero y resiliencia, evitando así las actividades empíricamente; por otro lado, los colaboradores deben cumplir con las normas empresariales y conllevar relaciones interpersonales para lograr un trabajo eficiente. Se trabajó con una muestra finita y se utilizó un instrumento elemental como lo es la encuesta para la debida recopilación de información. Se obtuvo como resultado 4 dimensiones imprescindibles en el estudio como lo son: habilidades y destrezas, perfil profesional, logro de objetivos y políticas internas las mismas que al desempeñarlas de forma efectiva dará paso a que las microempresas desarrollen una ventaja competitiva. Finalmente se concluyó que el personal de las microempresas no posee conocimiento óptimo en la gestión financiera.
Keywords: TALENTO HUMANO; GESTION FINANCIERA; COMPETENCIAS